Interlanguage of Error Analysis on Students Writing in Covid-19 Pandemic Era - Harahap, Winda Siska Perwana (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
This study aims to investigate the interlanguage of error analysis production on students writing. In writing process, there are general problem that occur such error from the interlanguage. This problem certainly getting worse during this Covid -19 pandemic era where the students only have limited direct or face to face English learning for one hour per week. Interlanguage is language used by second or foreign language when prosess of learning the target language. Data collected through documentation technique. The sample was taken using purposive sampling technique. There were five students as the sample. The framework of interlanguage and error analysis was applied in the process of data analysis. The results of this study indicate that the interlanguage of the students is influenced by 78% of language transfer, 10.5%of transfer of training and 10.5%of overgeneralization.